Pain assessment scales in newborns: integrative review - Gleicia Martins de Melo; Ana Luíza Paula de Aguiar Lélis; Alline Falconieri de Moura; Maria Vera Lúcia Moreira Leitão Cardoso; Viviane Martins da Silva (Sociedade de Pediatria de São Paulo, 2014)
OBJECTIVE: To analyze studies on methods used to assess pain in newborns.DATA SOURCES: Integrative review study of articles published from 2001 to 2012, carried out in the following databases: Scopus, PubMed, CINAHL, LILACS and Cochrane. The sample consisted of 13 articles with level of evidence 5.DATA SYNTHESIS: 29 pain assessment scales in newborns, including 13 one-dimensional and 16 multidimensional, that assess acute and prolonged pain in preterm and full-term infants were available in scientific publications.CONCLUSION: Based on the characteristics of scales, one cannot choose a single one as the most appropriate scale, as this choice will depend on gestational age, type of painful stimulus and the environment in which the infant is inserted. It is suggested the use of multidimensional or one-dimensional scales; however, they must be reliable and validated.